Princess and the Pea - Matthew Oldham (Usborne Publishing Ltd, 2018)
A lonely young prince wants to get married, but how can he find a real princess? This charming picture book retelling of Hans Christian Andersen$1 (Bs classic fairy tale, is brought to life with beautiful illustrations by Lorena Alvarez.s